2020
DOI: 10.1101/2020.08.03.20167833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol Generation from Different Wind Instruments

Abstract: The potential airborne transmission of COVID-19 has raised significant concerns regarding the safety of musical activities involving wind instruments. However, currently, there is a lack of systematic study and quantitative information of the aerosol generation during these instruments, which is crucial for offering risk assessment and the corresponding mitigation strategies for the reopening of these activities. Collaborating with 15 musicians from the Minnesota Orchestra, we conduct a systematic study of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…The saturation limit of the data collection device, 40 which is 210 particle/cm 3 , was never reached during our experiments. In the comparison, most of our results are in the same magnitude as the results of Alsved et al, 7 Gregson et al, 15 He et al, 17 Stockman et al, 18 and McCarthy et al 19 The differences might be caused by different sampling sizes, sample variances, and different measuring equipment and setups in each experiment. For the source air velocity, our measurements are comparable with Stockman et al, 18 Bahl et al, 20 and Becher et al 21 For the jet length, our measurements are in the same magnitude of the result from Becher et al 21 However, the plume influence distance is shorter than the result from Gantner et al 23 The differences may be caused by different experiment methods and setups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The saturation limit of the data collection device, 40 which is 210 particle/cm 3 , was never reached during our experiments. In the comparison, most of our results are in the same magnitude as the results of Alsved et al, 7 Gregson et al, 15 He et al, 17 Stockman et al, 18 and McCarthy et al 19 The differences might be caused by different sampling sizes, sample variances, and different measuring equipment and setups in each experiment. For the source air velocity, our measurements are comparable with Stockman et al, 18 Bahl et al, 20 and Becher et al 21 For the jet length, our measurements are in the same magnitude of the result from Becher et al 21 However, the plume influence distance is shorter than the result from Gantner et al 23 The differences may be caused by different experiment methods and setups.…”
Section: Discussionsupporting
confidence: 81%
“…Each musician directed their aerosol plumes into a metal funnel to further minimize influences of the ambient air during source aerosol concentration measurements. The funnel was also used to help collect particles in the related experimental studies on exhaled aerosols 15,17,24–26 . We prepared three funnels with diameters 10.4, 12.7, and 14.5 cm to fit various dimensions of the mouth and instrument outlet.…”
Section: Methodsmentioning
confidence: 99%
“…We find that the averaged number of aerosols produced by the trumpet (at the peak) is nearly twice as much as the clarinet. Aerosol emission data, φ (particles/m 3 ), also show that the trumpet produces more aerosols than the clarinet (1d, inset), in agreement with recent results [25]. This may be due to instrument construction material; the wood of the clarinet is able to retain more moisture than the metal alloy of the trumpet [28].…”
Section: Aerosol Productionsupporting
confidence: 86%
“…But even coughing and sneezing -where larger size (> 100 µm) particles move ballistically [20] at speeds reaching 5 − 10 m/s [21,22] -can be a factor in contamination, especially over shorter distances [14,15,23,24]. For wind musical instruments, studies have found distributions similar to speech (< 5 µm) [25], indicating the potential for long-range transport. Furthermore, recent experiments have shown the the flow created by some wind instruments can extend to approximately 30 cm away from the instrument [26]; ambient flow remains undisturbed at a distance > 1.5 m away from the instrument [27].…”
mentioning
confidence: 99%
“…But even coughing and sneezing -where larger size (> 100 µm) particles move ballistically [20] at speeds reaching 5 − 10 m/s [21,22] -can be a factor in contamination, especially over shorter distances [14,15,23,24]. For wind musical instruments, studies have found distributions similar to speech (< 5 µm) [25], indicating the potential for long-range transport. Furthermore, recent experiments have shown the the flow created by some wind instruments can extend to approximately 30 cm away from the instrument [26]; ambient flow remains undisturbed at a distance > 1.5 m away from the instrument [27].…”
mentioning
confidence: 99%